Pengaruh Beban Kerja terhadap Kinerja Karyawan Melalui Motivasi Kerja sebagai Variabel Intervening pada Perumda Air Minum Tirta Sakti Kabupaten Kerinci - Putra Abyan; Rohman Wilian; Dian Mala Fithriani Aira (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to determine the effect of the role of work motivation as a mediating variable between workload on employee performance at Perumda Air Minum Tirta Sakti, Kerinci Regency. The method used is quantitative analysis with data collection techniques by distributing questionnaires to 86 respondents. Data were collected using a Likert-scale-based questionnaire, and hypothesis testing used descriptive analysis techniques using SmartPLS 4 software. This study uses Outer Model testing, namely convergent Validity, Discriminant Validity, composite reliability and Inner Model testing, namely R-Square and Bootstrapping. The results of the study indicate that (1) workload has a positive and significant effect on employee performance. So the higher the workload, the higher the employee performance will be. (2) Workload has a positive and significant effect on work motivation. The higher the workload, the greater the motivation that arises in an employee. (3) Work motivation has a positive and significant effect on employee performance. If employees are motivated to work, their performance will be higher and improve. Conversely, if employees are less motivated, they will not be able to do their work well, so their performance will be less than optimal. (4) Work motivation can mediate between workload and employee performance. Employees who have high motivation can complete high workloads because this motivation encourages them to do their work with more enthusiasm and can determine efforts to achieve predetermined goals. e and Bootstrapping. The results of the study indicate that (1) workload has a positive and significant effect on employee performance. So the higher the workload, the higher the employee performance will be. (2) Workload has a positive and significant effect on work motivation. The higher the workload, the greater the motivation that arises in an employee. (3) Work motivation has a positive and significant effect on employee performance. If employees are motivated to work, their performance will be higher and improve. Conversely, if employees are less motivated, they will not be able to do their work well, so their performance will be less than optimal. (4) Work motivation can mediate between workload and employee performance. Employees who have high motivation can complete high workloads because this motivation encourages them to do their work with more enthusiasm and can determine efforts to achieve predetermined goals.